XI The Eleventh Toruń Pedagogical Students' Conference "Creatively Through Life - Innovative Forms of Development" Faculty of Educational Sciences, Uniwersytet Mikołaja Kopernika w Toruniu, 25.05.2017 - Martyna Lewandowska (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2018)
Reports